2000
DOI: 10.1016/s0306-4522(00)00063-4
|View full text |Cite
|
Sign up to set email alerts
|

Lemniscal recurrent and transcortical influences on cuneate neurons

Abstract: Intracellular recordings were obtained from cuneate neurons of chloralose-anesthetized, paralysed cats to study the synaptic responses induced by electrical stimulation of the contralateral medial lemniscus. From a total of 178 cells sampled, 109 were antidromically fired from the medial lemniscus, 82 of which showed spontaneous bursting activity. In contrast, the great majority (58/69) of the non-lemniscal neurons presented spontaneous single spike activity. Medial lemniscus stimulation induced recurrent exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 46 publications
1
36
0
3
Order By: Relevance
“…8 A, Control). This presumed recurrent suppression (Kelly and Renaud, 1973;Canedo et al, 2000) was observed at stimulating frequencies of up to 20 -25 Hz and was canceled by application of BiCu (Fig. 8 A, right) and/or strychnine.…”
Section: Effects Of Microiontophoresed Gaba And/or Glycinementioning
confidence: 88%
“…8 A, Control). This presumed recurrent suppression (Kelly and Renaud, 1973;Canedo et al, 2000) was observed at stimulating frequencies of up to 20 -25 Hz and was canceled by application of BiCu (Fig. 8 A, right) and/or strychnine.…”
Section: Effects Of Microiontophoresed Gaba And/or Glycinementioning
confidence: 88%
“…In this Section we explain how we modeled the circuit proposed by Canedo et al (2000) and shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it was also demonstrated that SMC could directly excite CT cells (Darian-Smith, 1966;Winter, 1965). Recent experiments in the cuneate nucleus, based on intracellular recordings in vivo Canedo et al, 2000) have confirmed the results of some of the classical studies, have questioned others and have added new insights about synaptic connections and relationships between the cerebral cortex and the CN. With regard to cuneate interneurons, in addition to excitatory effects, cortical inhibitory effects have also been observed .…”
Section: The Cuneate Nucleus and The Corticocuneate Circuitrymentioning
confidence: 97%
See 2 more Smart Citations